Towards a Theory of the Playgorm - Max Haiven (Media Theory)
This highly speculative paper proposes the term playgrom to identify an idiom of playfully cruel fascistic violence that emerges from, is shaped by, and also exceeds gamified financialized capitalism. Like the antisemitic pogroms of late-Tsarist Russia and subsequent acts of racist terrorism there and elsewhere, the playgrom appears to be a form of spontaneous, unsanctioned majoritarian mob violence against minorities. But we must look to the deeper roots of such phenomena in both dominant ideologies and collapsing socioeconomic systems. I draw on the examples of the 2014-15 Gamergate online decentralized anti-feminist swarming campaign and the 2019 Christchurch white supremacist massacre as examples of the playgrom. As others have illustrated, these acts of mass violence, which I will characterize as fascistic, were gamified, and drew on gaming themes, tropes and communities for their vitality. But I also propose that, to fully understand these phenomena, we must also contextualize them in the current moment of gamified capitalism, and so I propose approaching the playgrom as a form of deep, dark playbor.